2023
DOI: 10.18502/ijph.v52i3.12142
|View full text |Cite
|
Sign up to set email alerts
|

Measles Seroprevalence and Related Factors in Women Aged 15-49 Years Old, in Mersin, Turkey

Abstract: Background: If the mother is immune to measles, the infant is protected against measles infection after birth with maternal immunity. Therefore, the mother's immunity to measles is the most important factor in protecting the baby from measles in the first year. This study aimed to investigate measles seroprevalence and related factors in women between Oct 2019 and Jun 2021. Methods: The cross-sectional study was conducted on women aged 15-49 yr in Mersin city. Overall, 400 people were included in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…More recently, In Mersin, Turkey, a smaller cohort study investigated measles seroprevalence in women aged 15–49 years between Oct 2019 and Jun 2021 and found a 25.7% measles antibody seropositivity, suggesting that three out of every four babies born in the region were not adequately immunoprotected against measles. 22 Similarly, following a measles outbreak affecting several European countries including Greece during 2016–2018, two Greek seroprevalence studies found that around 13% of pregnant women were seronegative for measles antibodies. 23 , 24 Elsewhere, an African study conducted in Zambia during 2015–2017 among adult women of childbearing age found that 25% of women were seronegative.…”
Section: Recent Measles Seroprevalence Studiesmentioning
confidence: 99%
“…More recently, In Mersin, Turkey, a smaller cohort study investigated measles seroprevalence in women aged 15–49 years between Oct 2019 and Jun 2021 and found a 25.7% measles antibody seropositivity, suggesting that three out of every four babies born in the region were not adequately immunoprotected against measles. 22 Similarly, following a measles outbreak affecting several European countries including Greece during 2016–2018, two Greek seroprevalence studies found that around 13% of pregnant women were seronegative for measles antibodies. 23 , 24 Elsewhere, an African study conducted in Zambia during 2015–2017 among adult women of childbearing age found that 25% of women were seronegative.…”
Section: Recent Measles Seroprevalence Studiesmentioning
confidence: 99%